Trem das boas novas: uma análise socioantropológica do processo de institucionalização do culto nos trens de São Paulo - Lemos, Fernanda (2010)
The main objective of this thesis is to analyze, socio-anthropologically, the process of institutionalization of the evangelical worship carried out on the trains of São Paulo by the 'Interdenominational Evangelistic Crusade in the Good News Trains'. To achieve this main objective, we will seek to understand the relationship between religion and modernity, the train cult as an expression of contemporary religiosity, the relationships established between secular work and religious work, the motivational aspects for the daily and clandestine participation of subjects in the cult, and finally, the socio-anthropological aspects observed in its institutionalization process in its thirty years of existence. As a methodology, we will use, in addition to bibliographic research, field research, through the application of questionnaires and conducting interviews, considering their quantitative and qualitative aspects covered by the Social Sciences. Our main thesis is that the cult of the train has been undergoing a process of institutionalization, which can be observed from its origin, in its development and in its organization.(AU)